Development of Tempeh Packaging Mechanism: Paper Supply, Soybean Feeder and Mold Folded Part for Tempeh Wrapped with Paper - Wonga, Nor Aini (Progress in Engineering Application and Technology, 2023)
Tempeh is an Indonesian word that refers to a variety of fermented meals (mostly tender-cooked legumes) that have been held together into compact cakes by a dense mycelium of fragrant white Rhizopus moulds. Tempeh is often packaged manually using kraft paper in small industry, which takes a long time. The purpose of this project is to develop an automated Tempeh packaging system. Moreover, this study is focus more to create an idea for paper supply, soybean feeder, and folded part mechanism system, as well as design and build a prototype. The paper supply, soybean feeder, folded part, rubber band supply, and rubber bending part are the five key stations for the automated Tempeh system. However, this project is primarily focused on the paper supply, soybean feeder, and initial folded parts. SolidWorks software is used to create the prototype design. A few electrical parts are used to determine if the mechanism is effective or not, such as an Arduino Uno kit and servo motor. In term mechanism, for paper supply is inspire by paper printing machine. Besides, for soybean feeder part is gain from cat feeder mechanism. While, the inspiration for the folded part mechanism originated from a previous senior project, discussion, brainstorming and other sources such as YouTube. During the packaging of the tempeh, this system can also save time and costs. A healthy workplace may also be produced with this Tempeh packing technology. Overall, the conveyor works perfectly fine to deliver paper from the paper supply station to the soybean feeder station. While for paper supply part, it is also work perfectly fine to supply a piece of paper one by one. To supply soybean on the paper, the soybean feeder part of the component is working successfully. Hence, the mechanism of the prototype machine is 90 percent functional.